The experiences of living with a sibling who stutters: A preliminary study - Beilby, Janet; Byrnes, Michelle; Young, K. (Elsevier, 2012)
Stuttering impacts on the child in a variety of ways, notably in terms of communicative impairment and psychosocial impact. In addition, the stuttering disorder has a holistic impact, affecting those with whom the child who stutters lives. Within the family constellation, the closest person to the individual who stutters is often their sibling. This study investigated the experiences of fluent siblings of children who stutter to examine the impact that stuttering may have on their lives. A mixed methods research design incorporated qualitative semi-structured interviews and quantitative questionnaires. The results of the qualitative investigation revealed four aspects of children’s lives that were affected by having a sibling who stuttered: the relationship between siblings, the impact on the fluent sibling, the impact on the parent relationship with both children, and the impact on the sibling’s relationship with others. Findings revealed that siblings of children who stutter exhibited strongly negative emotions, and differing levels of responsibility associated with their involvement in the actual stuttering management programme. Furthermore, for the fluent sibling, secondary to having a brother or sister who stuttered, communication with and attention from their parents was variable. The results of the quantitative component of the study revealed children who stutter and their siblings demonstrated significantly greater closeness, and concurrently, increased conflict and status disparity than did the control fluent sibling dyads. The parents of the experimental sibling dyads also demonstrated significantly greater partiality towards a child, namely the child who stuttered, than did the parents of the control sibling dyads.